The Threatening of Rongga Language as a Result of Crossbreeding from Different Languages - Suparsa, I Nyoman; Mantra, Ida Bagus Nyoman; Apsari, Ni Putu Anggi (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
Several factors are causing the threat of a language, namely globalization, majority and minority ethnicities’s existence, lack of participation of the younger generation, and crossbreeding. One of the reasons for the Rongga language is crossbreeding. This study employed a qualitative research design to study the Rongga language in crossbreed marriages. Thus, this research is intended to analyze the crossbreeding between ethnic groups with different languages, especially to figure out how Manggarai-speaking people and Ngadha-speaking people who are married to Rongga people pronounce the words of the Rongga language that contain sounds ɓ, ɗ, ɠ, ᵐb, ⁿd, ᵑg, ɹ. This study found that the sounds [ɓ], [ɗ], [ɓ], [ᵐb], [ⁿd], [ᵑg], [ɹ] in the Rongga language by Manggarai speakers are pronounced as [bʰ], [dʰ], [gʰ], [mb], [nd], [ŋg], and [r]. Every language sound [ɓ], [ɗ], [ɠ], [ᵐb], [ⁿd], [ᵑg], [ɹ] in Rongga by speakers of the language Ngadha is respectively pronounced as [bʰ], [dʰ], [gʰ], [b], [d], [g], [ʤ] or [r]. It showed that the threat to the Rongga language started from the smallest elements, namely the sounds of the language. Apart from that, threats in the Rongga language also occurred due to the limited vocabulary in the Rongga language; hence, they had to absorb the vocabulary from Indonesian. This study implies communicating in Rongga language should be carefully taken into account because it has several language variations.